Comparing Radiation Doses in CBCT and Medical CT Imaging for Dental Applications - Jain Sulabh; Sarah; Mishra Shweta; Saleem Sumera; Vijayan Anu (Wolters Kluwer Medknow Publications, 2024)
BackgroundDental imaging plays a crucial role in diagnosis and treatment planning, with cone-beam computed tomography (CBCT) and medical computed tomography (CT) being two common modalities. This study aims to compare the radiation doses associated with CBCT and medical CT imaging in dental applications to assess their relative safety and efficacy. Materials and MethodsWe conducted a retrospective study using data from 100 patients who underwent both CBCT and medical CT scans for dental purposes. The radiation doses were measured in terms of dose-length product (DLP) for medical CT and dose-area product (DAP) for CBCT. The effective dose (ED) was calculated using appropriate conversion factors. Patient demographics, scan parameters, and radiation doses were recorded and analyzed. ResultsThe results indicated that the mean DLP for medical CT scans was 220 mGycm, whereas the mean DAP for CBCT scans was 150 mGycm². The corresponding mean effective doses for medical CT and CBCT were 2.5 mSv and 1.8 mSv, respectively. The radiation dose from CBCT was found to be approximately 28% lower than that from medical CT. ConclusionThis study demonstrates that CBCT imaging for dental applications results in significantly lower radiation doses compared to medical CT. While both modalities provide valuable diagnostic information, the choice of imaging technique should consider the balance between diagnostic quality and radiation exposure, especially for pediatric and high-risk patients. Dental practitioners should be aware of the potential dose reduction benefits associated with CBCT when appropriate for the clinical scenario.